PHENOLOGY AND YIELD OF THORNLESS BLACKBEERY CV. XAVANTE IN THE REGION OF GUARAPUAVA-PR - BOTELHO, Renato Vasconcelos; PAVANELLO, Alexandre Pozzobom; BROETTO, Doglas; SCISLOSKI, Scheila de Fátima; BALDISSERA, Tiago Celso (Scientia Agraria, 2009)
This work aimed to evaluate the behavior of thornless blackberry plants cv. Xavante in Guarapuava (PR), Brazil in 2005, 2006 and 2007. Twenty plants were weekly evaluated for sprouting percentage, and anthesis percentage. The blackberries were harvest twice or three times per week and in the first two seasons the fruits were evaluated for fruit weight and soluble solids content. The blackberry plants cv Xavante showed good adaptability in Guarapuava-PR, with regular sprouting between second-half of August and end of September, anthesis from beginning of October and middle of November and harvest between end of November and end of January. The estimated yield was between 2,790.5 and 5,952.9 kg ha-1, the fruit mean weight was 4,3 and 5,1 g and the soluble solids content was 8,3 and 10,1%.